1997
DOI: 10.1097/00006123-199702000-00038
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Consideration of a "Blister-like" Aneurysm at the Superior Wall of the Internal Carotid Artery: Case Report

Abstract: The blister-like aneurysm appeared to be a laceration of the carotid wall based on degeneration of the internal elastic lamina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
159
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 239 publications
(170 citation statements)
references
References 11 publications
2
159
1
Order By: Relevance
“…Inadequate treatment may result in recurrence and rebleeding frequently. According to a pathological report, 2) BBAs lack collagen tissues, fibrosis of adventitia, and inflammatory reactions, which can be observed in typical saccular aneurysms. Although the exact pathogenesis is not known, they are considered pseudoaneurysms resulting from the laceration and necrosis of dorsal ICA wall.…”
Section: Department Of Neurosurgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Inadequate treatment may result in recurrence and rebleeding frequently. According to a pathological report, 2) BBAs lack collagen tissues, fibrosis of adventitia, and inflammatory reactions, which can be observed in typical saccular aneurysms. Although the exact pathogenesis is not known, they are considered pseudoaneurysms resulting from the laceration and necrosis of dorsal ICA wall.…”
Section: Department Of Neurosurgerymentioning
confidence: 99%
“…5) Several surgical techniques have been advocated to securely close the rupture point with preservation of the blood flow in the ICA, including parallel clipping, 10) suturing, 16) covering the aneurysm with an encircling clip, 14) vascular closure stapling, 15) and the so-called``wrap-clipping'' technique. 1,2,8,11,12) However, removal of subarachnoid clots surrounding the intracranial ICA is required prior to procedures involving the lesion, including trapping. Blister-like aneurysms of the ICA are prone to rupture during such procedures due to the fragility of the aneurysm walls, which are covered with adventitia and clot or only clot.…”
Section: Introductionmentioning
confidence: 99%
“…Results of an autopsy indicated that BBAs are focal wall defects covered by a thin layer of fibrous tissue and adventitia and lack the usual collagenous layer. 6 Therefore, these aneurysms have a high risk of premature rupture during surgery and are associated with the development of large lacerations on the parent vessel during microsurgery, both of which may result in a poor outcome. 1 It has also been reported that BBAs occur predominantly on the right side and in females.…”
Section: Clinical Features Of Bbasmentioning
confidence: 99%
“…1 It has also been reported that BBAs occur predominantly on the right side and in females. 13 Frequently, these lesions are associated with hypertension, 13,14,20 arteriosclerosis, 1,6,20 and ICA dissection. 14 In our study, more than one half of the patients had BBAs on the right side and a history of hypertension, findings that resemble those of others.…”
Section: Clinical Features Of Bbasmentioning
confidence: 99%
“…8,18) Nonatherosclerotic aneurysms unrelated to the branching zones can be classified into the following four types, based on the pathological patterns of the internal elastic lamina and the state of the intima: classic dissecting aneurysm (widespread disruption of the internal elastic lamina without intimal thickening), segmental ectasia (stretched/fragmented internal elastic lamina with intimal thickening), dolichoectatic dissecting aneurysm (fragmented internal elastic lamina and multiple dissections of the thickened intima), and saccular aneurysm (minimal disruption of the internal elastic lamina without intimal thickening). 13) In the present case, the histological examination demonstrated a saccular aneurysm, although hemodynamic stress was unlikely to have affected the formation of the aneurysm according to the angiographical findings.…”
Section: Discussionmentioning
confidence: 99%